O Powstawaniu Wyboczenia Prętów Prostych - Wierzbicki, W. (Engineering Transactions, 1953)
This work is based to a large extent on twelve papers by the same author, which are listed in the introduction. In the first section a definition of buckling in the technical sens is given as the phenomenon of deflection of a straight bar submitted to axial compression when the longitudinal force exceeds a certain value, called «critical». The terms «straight» and «axial» are to be understood as defined by the accuracy of measurements. The author shows that the above mentioned definition includes all kinds of buckling, in the mathematical as well as in the physical sense, of elastic and non-elastic bodies. All these cases are discussed on the basis of experiments made at various times, and taking into consideration the calculations of the deformation of a straight bar subjected to simultaneous bending and compression. The notion of quasi-unstable equilibrium is introduced for the state resembling, from the point of view of kinematics, the unstable equilibrium and from the energetic point of view, the stable equilibrium. An example of the above defined state of equilibrium is the case of unpermissibly large deflections of a straight bar caused by the action of longitudinal forces (the phenomena of quasi-buckling).Section II contains an analysis of certain models of buckling and quasi-buckling. One of them is Southwell's cylindrical model, while the other six are the author's own models.In section III the relation between buckling and eccentrical com- pression is discussed. This problem is of special importance in the in the case of lattice bars, and is discussed in a separate paragraph. An analysis is given of the formula derived by F. Jasiński for simultaneous bending and compression. In section IV, after taking into consideration the sections reviewed, the author proposes a general definition of buckling as being a case of unstable or quasi-unstable equilibrium.